Symptoms-modifying effects of electromotive administration of glucosamine sulphate among patients with knee osteoarthritis - Ayodele Teslim Onigbinde; Adegbenga Rotimi Owolabi; Kamil Lasisi; Oghenekewe Isaac Sarah; Adeoye Folorunsho Ibikunle (World Scientific Publishing, 2018)
Background: Most trials on symptom-modifying effects of glucosamine are limited to administration through oral route with dearth of empirical data on the use of electromotive force. Objective: The study determined the effects of glucosamine sulphate (GS) iontophoresis (IoT) on radiographic parameters of patients with knee osteoarthritis (OA). Methods: Fifty-three patients were randomly assigned to three groups. About 1g each of GS was administered using IoT and cross-friction massage (CFM) for participants in groups 1 (IoT) and 2 (CFM), respectively. Group 3 ((Combined therapy) CoT) received 1g of GS using both IoT and CFM. Interventions were twice a week for 12 weeks. Analysis of variance (ANOVA) was used to analyze the data (p<0.05). Results: After 12 weeks, the medial joint space width (JSW) of the CFM group was significantly higher than that of IoT and CoT groups (p=0.005 and p=0.004). Lateral JSW of IoT group was significantly higher than both CFM (p=0.001) and CoT groups (p=0.01). There were significant decreases in pain intensities; increase in knee flexion and physical functions across the groups (F=9.33,p=0.01;F=3.23,p=0.01; H=4.97,p=0.01, respectively). Conclusion: It was concluded that there were significant decreases in the degenerative changes at the knee joint.